The Proline-mediated Reactions of Tobacco Plants, Cultivated Under Salinity (Notes in Current Biology, 2016)
The comparative investigation of tobacco plants reactions on lethal salinity pressure and their proline status were the objects of the research.On selective media with the addition of lethal for cell cultures doses of Ba2+ cations resistant tobacco cell lines occurred. Regenerants R0 and seed progenies R1, R2 were obtained from those lines. Cell lines, R0, R1 and R2 plants challenged the simulated lethal salt stresses. The comparative investigation of proline-mediated reactions of those variants and initial tobacco (pure glicophyte) were elaborated. R0 plants were cultivated in vitro during 35 days on cultural media with the addition of 20,0g/l sea water salts; R1 and R2 plants were tested in water culture with the addition of 25,0 g/l sea water salt during 10 days.Control and experimentally obtained variants developed different reactions to salt pressure. Control plants eliminated. Experimental variants maintained their metabolism reflected in stable protein biosynthesis. At the same time the free proline levels increased in all genotypes. But in resistant variants these events resulted from amino acid biosynthesis, while in control plants proline appearance was the result of the protein compartments degradation. So data of free proline level are not adequate markers of the plant salt resistance. There is better to estimate the character of proline changes.